Determination of U3O8 in UO2 by infrared spectroscopy - Liliane Aparecida Silva; Fernando Soares Lameiras; Ana Maria Matildes dos Santos; Wilmar Barbosa Ferraz; João Batista Santos Barbosa (REM: International Engineering Journal)
Abstract The oxygen-uranium (O-U) system has various oxides, such as UO2, U4O9, U3O8, and UO3. Uranium dioxide is the most important one because it is used as nuclear fuel in nuclear power plants. UO2 can have a wide stoichiometric variation due to excess or deficiency of oxygen in its crystal lattice, which can cause significant modifications of its proprieties. O/U relation determination by gravimetry cannot differentiate a stoichiometric deviation from contents of other uranium oxides in UO2. The presence of other oxides in the manufacturing of UO2 powder or sintered pellets is a critical factor. Fourier Transform Infrared Spectroscopy (FTIR) was used to identify U3O8 in samples of UO2 powder. UO2 can be identified by bands at 340 cm-1 and 470 cm-1, and U3O8 and UO3 by bands at 735 cm-1, 910 cm-1, respectively. The methodology for sample preparation for FTIR spectra acquisition is presented, as well as the calibration for quantitative measurement of U3O8 in UO2. The content of U3O8 in partially calcined samples of UO2 powder was measured by FTIR with good agreement with X-rays diffractometry (XRD).